The Self-Help Book in the Therapeutic Ontosphere: A Postmodern Paradox - Collingsworth, Jean (Culture Unbound, 2014)
he self-help book is a prominent cultural and commercial phenomenon in the therapeutic ontosphere which permeates contemporary life. The generic term ’ontosphere’ is here co-opted from IT to describe a notional social space in which influential conceptualisations and shared assumptions about personal values and entitlements operate without interrogation in the demotic apprehension of ’’. It thus complements the established critical terms ’discourse’ and ’episteme’. In the therapeutic ontosphere the normal vicissitudes of life are increasingly interpreted as personal catastrophes. As new issues of concern are defined, it is assumed that an individual will need help to deal with them and live successfully. Advice-giving has become big business and the self-help book is now an important post-modern commodity. However a paradox emerges when the content and ideology of this apparently postmodern artifact is examined. In its topical eclecticism the genre is indeed unaligned with those traditional ’grand narratives’ and collective value systems which the postmodern critical project has sought to discredit. It endorses relativism, celebrates reflexivity and valorizes many kinds of ’personal truth’. Moreover readers are encouraged towards self-renovation through a process of ’bricolage’ which involves selecting advice from a diverse ethical menu along-side which many ’little narratives’ of localized lived experience are presented as supportive exemplars. However in asserting the pragmatic power of individual instrumentality in an episteme which has seen the critical decentering of the human subject, the self-help book perpetuates the liberal-humanist notion of an essential personal identity whose stable core is axiomatic in traditional ethical advice. And the heroic journey of self-actualization is surely the grandest of grand narratives: the monomyth. Thus the telic self-help book presents the critical theorist with something of a paradox.